Substrate dependent reaction channels of the Wolff–Kishner reduction reaction: A theoretical study - Yamabe, Shinichi; Zeng, Guixiang; Guan, Wei; Sakaki, Shigeyoshi (Beilstein Journal of Organic Chemistry, 2014)
Wolff–Kishner reduction reactions were investigated by DFT calculations for the first time. B3LYP/6-311+G(d,p) SCRF=(PCM, solvent = 1,2-ethanediol) optimizations were carried out. To investigate the role of the base catalyst, the base-free reaction was examined by the use of acetone, hydrazine (H2N–NH2) and (H2O)8. A ready reaction channel of acetone → acetone hydrazine (Me2C=N–NH2) was obtained. The channel involves two likely proton-transfer routes. However, it was found that the base-free reaction was unlikely at the N2 extrusion step from the isopropyl diimine intermediate (Me2C(H)–N=N–H). Two base-catalyzed reactions were investigated by models of the ketone, H2N–NH2 and OH−(H2O)7. Here, ketones are acetone and acetophenone. While routes of the ketone → hydrazone → diimine are similar, those from the diimines are different. From the isopropyl diimine, the N2 extrusion and the C–H bond formation takes place concomitantly. The concomitance leads to the propane product concertedly. From the (1-phenyl)ethyl substituted diimine, a carbanion intermediate is formed. The para carbon of the phenyl ring of the anion is subject to the protonation, which leads to a 3-ethylidene-1,4-cyclohexadiene intermediate. Its [1,5]-hydrogen migration gives the ethylbenzene product. For both ketone substrates, the diimines undergoing E2 reactions were found to be key intermediates.
Keywords: acetone; acetophenone; DFT calculations; diimine intermediate; reduction reaction; transition states; Wolff–Kishner